The predictors of adopting cloud computing e-learning in Iraq: the role of technology readiness - Zainab Dalaf Katheeth; Bashar Alathari; Ammar Dheyaa Noor (Bulletin of Electrical Engineering and Informatics, 2022)
Cloud computing electronic learning (CCEL) is a new technology that enables educators and students to extend the storage and access learning materials. The use of this technology is limited worldwide. However, in the time of COVID 19, this technology becomes essential for the educational processes. The purpose of this study is to examine the predictors of using CCEL among academic staff and students in Iraq. Based on literature, this study proposed that perceived ease of use (PEOU), perceived usefulness (PU), and subjective norms (SN) will affect the intention to use (IU) which in turn will affect the actual use (AU). Attitude (AT) is proposed to mediate the relationships while technology readiness (TR) is proposed as a moderator. The data is collected from 331 students and academic staff in three Iraqi universities using stratified sampling. Data analysis is conducted using SmartPLS. The results showed that PEOU, PU, and SN affect positively IU which in turn affected AU. AT mediated partially the effect of PEOU, PU, and SN on IU while TR moderated only the effect of PEOU on IU. Decision makers are recommended to simplify the usage of CCEL and to conduct workshops about the usage and benefits of CCEL.